Geological structure, ore-metasomatic and mineralogical geochemical zoning of Au-Mo-Cu porphyry Kyzyk-Chadr deposit, Tyva republic: DOI: 10.47765/0869-5997-2021-10004 - Андреев Антон Вадимович; Гирфанов Михаил Миргалимович; Старостин Иван Александрович; Авилова Ольга Владимировна; Кряжев Сергей Гаврилович; Юрмазов Дмитрий Николаевич; Бабкин Игорь Александрович; Семёнов Михаил Иванович (Ores and Metals (Rudy i metally), 2021)
Major geological structure features, ore and metasomatic composition, ore-metasomatic and isotope-geochemical zoning are considered for Kyzyk-Chadr deposit within the namesake ore cluster of Ozhinsky ore district, Altai-Sayany mineragenic province. A set of geological and prospecting evidence (elements of the deposit geological and prospecting model) was defined; it can be used to improve the efficiency of further exploration within Sayany-Altai region prospects.